European justice as the last resort for the polish judiciary: CJEU against the arbitrary lowering of the retirement age of judges. Commentary on the judgment of 24 june 2019, Commission v. Poland, C-619/18 - Krzywoń, Adam (Journal of the Basque Parliament, 2020)
In the judgment of 24 June 2019, Commission v. Poland (Independence of the Supreme Court), C-619/18, EU:C:2019:531, the Court of Justice of the European Union ruled on the retirement of Polish Supreme Court judges, declaring that the mechanism of arbitrarily lowering the retirement age was contrary to the European Union law. This commentary analyses the latest changes in the Polish judicial system and the context of the CJEU ruling. The study is focused in the change in European case-law and the development of instruments available to the EU institutions for monitoring judicial independence. The paper discusses also the elements of the judicial independence indicated by CJEU and the rules on the retirement of judges.